1971
DOI: 10.1161/01.res.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Reentry in Canine Ventricular Tissue

Abstract: In isolated canine papillary muscle-false tendon preparations it was possible by selecting the pattern of stimulation to obtain conduction block within the peripheral distribution of the Purkinje network. Action potentials recorded just proximal to the site of block were always extremely brief in duration; refractory periods were abbreviated accordingly. When propagation from specialized fibers to muscle fibers was made very critical, conduction block occurred at some Purkinje-muscle junctions while propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
3

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(49 citation statements)
references
References 12 publications
6
40
0
3
Order By: Relevance
“…Since conduction block at Purkinje-muscle junctions frequently is unidirectional,9' 11, 13, 14 postoverdrive Purkinje-muscle conduction block could be conducive to the development of reentry. 26 Limitations. Since the passive membrane properties of cells at the Purkinje-muscle junction are unknown, it is not possible to calculate the charge required for activation of junctional cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since conduction block at Purkinje-muscle junctions frequently is unidirectional,9' 11, 13, 14 postoverdrive Purkinje-muscle conduction block could be conducive to the development of reentry. 26 Limitations. Since the passive membrane properties of cells at the Purkinje-muscle junction are unknown, it is not possible to calculate the charge required for activation of junctional cells.…”
Section: Discussionmentioning
confidence: 99%
“…A propensity for unidirectional conduction block at the PVJs has been well described in pacing studies. 18,19,35 This block sets the stage for Purkinjemuscle reentrant excitation, 36 which has been recently implicated as a mechanism of polymorphic ventricular arrhythmias in simulation studies. 37 Our data suggest that both conduction block (leading to wave splitting) and reentry at the PM root could have had the participation of PVJ, further confirming the relevance of the Purkinje system during VF.…”
Section: Tissue Heterogeneity Intramyocardial Purkinje Fibers and Wmentioning
confidence: 99%
“…Conduction disturbance at P-V junctions can occur under various pathological states, especially under ischemic conditions, e.g., hypoxia, hyperkalemia, and acidosis [12]. Impairment of electrical coupling at the P-V junction provides an opportunity to create a reentrant circuit of excitation, an important substrate for the development of ventricular tachyarrhythmias [21,34,39]. Microelectrode recording also suggested that ventricular arrhythmias in acute ischemia arise from ectopic focal excitation within the Purkinje-fiber network of the peri-infarct zone [17].…”
Section: Electrophysiological Aspects Of Purkinjeventricular Musclmentioning
confidence: 99%